2001
DOI: 10.1055/s-2001-14899
|View full text |Cite
|
Sign up to set email alerts
|

Urodynamic Findings in the Tethered Spinal Cord: The Effect of Tethered Cord Division on Lower Urinary Tract Functions*

Abstract: Lower urinary tract dysfunctions secondary to tethered cord syndrome are very common in spinal dysraphic cases and significant improvements can be achieved with a judiciously timed division of the spinal tethered cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…[39][40][41] Among surgical studies (n = 12), there was no clear or standardized description in the untethering technique utilized. [30][31][32][33][34]37,38,[42][43][44] Among these surgical studies, only 6 described their complications in the results section of the respective article. Additionally, 5 out of the 13 studies did not provide information on the length of follow-up after surgical intervention.…”
Section: Description Of Evaluation Results and Follow-upmentioning
confidence: 99%
See 3 more Smart Citations
“…[39][40][41] Among surgical studies (n = 12), there was no clear or standardized description in the untethering technique utilized. [30][31][32][33][34]37,38,[42][43][44] Among these surgical studies, only 6 described their complications in the results section of the respective article. Additionally, 5 out of the 13 studies did not provide information on the length of follow-up after surgical intervention.…”
Section: Description Of Evaluation Results and Follow-upmentioning
confidence: 99%
“…In our systematic review, we observed differences in the diagnostic criteria of TCS and widely variable health outcomes following surgery in Asian countries. 31,[38][39][40] Our findings suggest that among studies conducted in this region, the management of TCS was aggressive in the surgical approach leading to untethering and often did not rely on the pres-ence of progressive neurologic deficits as a criterion for initial surgical treatment of spinal cord tethering. 30,33,34,42 To address the observable variation in the diagnostic criteria for TCS, Lew and Kothbauer 26 defined TCS as "a diverse clinical entity which presents with symptoms and signs resulting from abnormal spinal cord tension. "…”
Section: Global Surgery and Variance In Surgical Approach To Tcsmentioning
confidence: 90%
See 2 more Smart Citations
“…There seems to be a consensus among authors that SSCU surgery leads to improvement in urological dysfunctions in children with TCS after surgical release [9][10][11][12]15 .…”
Section: Introductionmentioning
confidence: 99%